Asymptotic Behavior of Switched Stochastic Delayed Cellular Neural Networks via Average Dwell Time Method - Hanfeng Kuang; Jinbo Liu; Xi Chen; Jie Mao; Linjie He (Abstract and Applied Analysis)
The asymptotic behavior of a class of switched stochastic cellular neural networks (CNNs) with mixed delays (discrete time-varying delays and distributed time-varying delays) is investigated in this paper. Employing the average dwell time approach (ADT), stochastic analysis technology, and linear matrix inequalities technique (LMI), some novel sufficient conditions on the issue of asymptotic behavior (the mean-square ultimate boundedness, the existence of an attractor, and the mean-square exponential stability) are established. A numerical example is provided to illustrate the effectiveness of the proposed results.